Computational Analysis Of Pipe Bend Angle Effect On Pressure Drop - Akbar, Muhammad Khoirul; Roihatin, Anis; Aulia, Nur Fatowil (Politeknik Negeri Lhokseumawe, 2024)
The air conditioning system is a significant energy source inskyscrapersfor supplying cool air to all rooms. However, the process has energy losses due to the ducting used. If the problem of energy loss can be solved, the air conditioning system will bring advantages in terms of energy efficiency and financial savings. A pressure drop in air duct pipe installations, such as pipe bends, is one type of energy loss. This research intends to use Computational Fluid Dynamics (CFD) to investigate the effect of pipe bend angles and velocity relationships on pressure drop in air duct pipe installations, which has previously been validated by experimental research with a 0.17% error percentage. This study focuses on square pipe bends with varying 45o, 60o, and 90o bend angles. The research showed that when testing the highest fluid velocity of 19.68 m/s, the highest pressure drop was 275.69 Pa on the pipe bend angle of 90o, while the lowest pressure drop was 256.41 Pa on the pipe bend angle of 45o. When testing the lowest fluid velocity of 9.77 m/s the highest pressure drop was 67.73 Pa on the pipe bending angle of 90owhile the lowest pressure drop was 62.98 Pa on thepipe bending angle of 45o. The simulation results indicate that the larger pipe bend angle result in a higherpressure drop, and vice versa.